A study on employee engagement towards citizen centric public service excellence / Norazlin Mohd Nor - Mohd Nor, Norazlin (2019)
The Malaysian government was once dubbed as the Asian Tiger during the 1990s. Sadly today, the public sector is no longer respected and the administrators are no longer held in high regard. Some have even called the public sector as directionless, huge, and inefficient. Realising this, the Prime Minister has called for the government to become citizen centric. A citizen centric government is a concept that promotes the involvement of citizens in all key decisions of the public sector. By becoming citizen centric, the Malaysian government may address citizens’ needs and demands and provide attention to matters that are of the public interests. However, the biggest challenge faced by the Malaysian public sector is to shape an institutional culture that supports this delivery concept. For decades, the norm for public sector employees is to follow order and take directive, without question or hesitation. Any challenges made to the decision makers are not well received. Due to this, the public sector is faced with situations that devalue its employees which have created a sense of resentment and bitterness, thus contributing to the public sector’s defection and deficiency. There are many factors that contribute to becoming citizen centric and these factors relate strongly with employees’ antecedents of engagement. It is believed that by valuing and taking care of the employees first, they are able to perform with passion and beyond expectations, subsequently influence organisational effectiveness and therefore, drive towards excellence. Taking these considerations, the main purpose of this study is to ascertain the level of citizen centric, investigate the relationship between predictors of engagement and citizen centric, and identify the predictor that has the most significant impact towards citizen centric public service excellence in Malaysia. A 5-point Likert scale questionnaire was distributed to Administrative and Diplomatic Officers serving the federal government located in Kuala Lumpur and Putrajaya. Four hundred and twenty-eight responses were recorded and analysed using SPSS software version 24. The results indicated that 79.48% of respondents agree that the public sector is in line with the aspiration of becoming citizen centric. As such, the level of citizen centric public service excellence in Malaysia is statistically high with an overall mean score of 3.94. Additionally, the aspects of people, products, partnerships and resources; strategy; work environment; well-being; and work-life balance have been proven statistically to contribute positively and significantly towards building citizen centric public service excellence in Malaysia. The aspect of people, products, partnerships and resource is identified as the most influencing factor with standardised coefficient value of 0.252. One factor however, is found to be insignificant. Although numerous studies have indicated that leadership contributes to organisational success, the result for this study showcased otherwise. In fact, the results also proposed that 50.8% of citizen centric public service excellence is contributed by other factors such as job satisfaction or advancement of ICT, which are often influenced by employees’ personality, behaviour and experience, and cannot be controlled by the organisation. This study concludes by introducing a Citizen Centric Public Service Excellence Model that can be used as a holistic and comprehensive model that promotes the importance of taking care of employees first. The model can be reproduced to address fluctuating issues, trends and challenges where in the long run, provides flexibility for public organisations to continuously adapt to changes and move together with the people.